PENGARUH LATIHAN TEPUKAN DRIBBLE TERHADAP KEMAMPUAN DRIBBLING TIM U-15 SSB CHEVRON PEKANBARU - Irfansyah, Ahmad Viqar; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study to determine the influence of exercise a pat dribble to the ability to dribbling the team u-15 ssb Chevron Pekanbaru. In this study researchers took population of the u-15 ssb Chevron Pekanbaru which amounted to 16 people. The sample in this study, using techniques of sampling used is a sample of saturated and that’s where all the population as a sample. The design of this study uses a group of the research is wearing the one group pretest-posttest design. The insrument was done in this study to measure the ability of the dribbling the way dribbling the test over the hurdle. After that, the data processed by the statistics, to test the normality by lilifors test at a significant level of α (0.05). This hypothesis put forward is the influence of a pat dribble to the ability to dribbling. Based on statistical data analysis, it yields pretest data Lcount 0,1170, data posttest Lcount 0,1397 and Ltabel 0,213, mean Lcount < Ltabel. Then the data is normally distributed. Based on t test analysis yielded Tcount equal to 2,91 and Ttabel 1,75, mean Tcount> Ttabel .Thus, there is the of a dribble pat on the dribbling ability of team u-15 ssb Chevron Pekanbaru.Key Words: Dribble pat, Skill dribbling